Combined Homing Guidance Law of Torpedo Based on Fuzzy Control - Baoming MU; Jianqing CHENG; Feng PAN (水下无人系统学报)
In the process of torpedo homing guidance, it is difficult for a single guidance method to adapt to different guidance phases and ensure the torpedo guidance effect effectively. For this reason, this paper designs a fuzzy combined guidance law based on the principle of fuzzy control by combining three different typical guidance methods, namely, fixed lead angle guidance method, proportional guidance method, and variable structure guidance method. The results of simulation and comparison in different environments show that the comprehensive performance of the fuzzy combined guidance law is better than that of other typical guidance laws, which can provide reference for the practical application of torpedo homing guidance.